Implementation of Competence-Based Human Resources Management in the Digital Era - Dolan, Ellen; Kosasi, Sandy; Sari, Siti Nurindah (Pandawan Sejahtera Indonesia, 2022)
Human resource management digitization may help businesses update their HR processes and provide them a competitive edge. At the same time, it demands a change in work style and a change in the necessity for Human Resources. The purpose of the study is to determine how competency-based human resource management may be used in the digital age. Additionally, researchers examine the primary advantages and disadvantages of the present situation and examine how they affect the skills and roles of HR professionals. Analysis of secondary data characterizing the degree of current digital proficiency based on the responses of more than 7,000 respondents from six EU member nations is part of the qualitative research (Germany, Finland, UK, Portugal, Sweden and Slovakia). The findings show that professional HR applications are typically hesitant to incorporate new technology. Future scholars should note that this study solely focuses on how human resource management is used in the digital age. Therefore, further in-depth study on this issue may be carried out by choosing a larger focal area.